Variations of malondialdehyde in pre-eclampsia. (2nd July 2016) - Khoubnasabjafari, Maryam; Ansarin, Khalil; Jouyban, Abolghasem
ABSTRACT: Malondialdehyde, as a biomarker of oxidative stress in pre-eclampsia, is discussed in terms of the determination methods, the validity of the obtained data, and variations in different studies, and it is concluded that there is a need for re-validation of the analytical methods and re-evaluation of its role as a biomarker of oxidative stress.